(untitled) (Research, Society and Development, 2022)
Ventilator-associated pneumonia (VAP) is a nosocomial infection considered one of the most common within the Intensive Care Unit, with an incidence of 6 to 50 cases per 100 hospitalizations in this environment. The current study, taking into account the scientific literature, aims to show the risk factors for the development of ventilator-associated pneumonia in ICU patients. This is an integrative literature review, carried out in May and June 2022 through electronic searches in the Google Scholar database. The search strategies allowed the identification of 984 articles, applying the inclusion criteria, 975 were excluded, in total 9 articles were selected because they met all the requirements. The results show that tracheal intubation and reintubation, shock, the advance of Chronic Obstructive Pulmonary Disease, exogenous contamination and antibiotic therapy as prophylaxis are considered aspects that favor the emergence of pneumonia associated with mechanical ventilation. It is concluded that it is extremely important to know the aspects that increase the chance of occurrence of such a problem, so that you can develop, prevent and develop measures that help to minimize damage to the health of the individual.